PENGATURAN TENTANG ARBITRASE AD HOC DALAM UNDANG-UNDANG NOMOR 30 TAHUN 1999 TENTANG ARBITRASE DAN ALTERNATIF PENYELESAIAN SENGKETA - Antono Antono (Program Magister Hukum Universitas Lambung Mangkurat, 2017)
Article 6 paragraph (9) of Act Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution as positive law stipulates that if the peaceful effort cannot be reached, then the parties based on written agreement may refer the settlement of their dispute through insitutional arbitration or ad hoc arbitration. Act Number 30 of 1999 does regulate not clearly and expressly on ad hoc arbitration. Seemingly, Act Number 30 of 1999 is more oriented to institutional arbitration. In Indonesia there are a number of institutional arbitration such as BANI, BASYARNAS, and BAPMI. This research is normative legal research. The type of the research is vague norm and the approaches applied are statute approach and comparative approach.The results of the research are as follows: firstly, Act Number 30 of 1999 regulates more on institutional arbitration and regulates relatively less on ad hoc arbitration. There are not sufficient regulation on the recruitment so it is not clear what the criteria and procedure of recruitment of ad hoc arbitrators. The position of the ad hoc arbitrators is unclear; the office or domicile of the ad hoc arbitration is unknown, thus, it makes difficult for the society who want to bring their disputes to the ad hoc arbitration. It is different from institusional one which has its own arbitration law of procedure (lex atribtri), ad hoc arbitration does not possess it own arbitration law of procedure (lex atribtri). The executorial power of the award made by ad hoc arbitration is still dilematic and its registration at the District Court is still hindered because the District Court is still reluctant to recognize the award of ad hoc arbitration. It is so because ad hoc arbitration is considered not so credible and the District Court does trust it because its existence is not clear. If an award is not registered at the District Court which is proven with the presence of Registration Deed issued by the District Court so such arbitral award can not be executed (does not have executorial power).